Long-wavelength visible to near infrared photoluminescence from carbon-bridged styrylstilbene and thiadiazole conjugates in organic and aqueous media. Issue 11 (3rd February 2021) - Inoue, Takeru; Tsurui, Makoto; Yamagishi, Hiroshi; Nakazawa, Yuma; Hamaguchi, Naoto; Watanabe, Shoya; Kitagawa, Yuichi; Hasegawa, Yasuchika; Yamamoto, Yohei; Tsuji, Hayato
Abstract : Efficient long-wavelength visible to NIR-emitting materials have been synthesized by use of rigid planar styrylstilbene as a donor component. Abstract : Donor–acceptor–donor conjugates composed of electron-donating carbon-bridged styrylstilbene (COPV2) and electron-accepting thiadiazole derivatives equipped with carbazolyl (Cz) terminators, Cz-COPV2-A-COPV2-Cz (A = benzothiadiazole (BTz ), naphthobis(thiadiazole) (NTz ), or benzobis(thiadiazole) (BBTz )), were newly synthesized and found to serve as efficient and stable long-wavelength photoluminescent dyes in organic and aqueous media. In particular, Cz-COPV2-BBTz-COPV2-Cz showed photoluminescence in the near infrared region (895–927 nm) with a photoluminescence quantum yield (PLQY) of up to 0.19 in cyclohexane and of 0.02–0.03 in THF/water mixtures. Its analogues with weaker acceptors, Cz-COPV2-BTz-COPV2-Cz and Cz-COPV2-NTz-COPV2-Cz, showed yellow to deep-red emission in organic solvents, with PLQYs of up to 0.71 in organic solvents and 0.45 in THF/water mixtures.